Development and application of 3D printing technology in various fields. (August 2019) - Chen, Wanlu; Zhang, Yi
Abstract: As a cutting-edge and pioneering emerging technology, 3D printing technology is profoundly changing the traditional production mode and production process. This paper analyzes the development of 3D printing technology at home and abroad in recent years, as well as its application in various fields, focusing on the application and development prospect of 3D printing technology in the field of mechanical engineering.